Diversidade e estrutura trófica das assembléias de peixes antes da implantação de uma barragem em um rio neotropical - Pini, Suelen Fernanda Ranucci (2020)
In the upstream region to the Iguaçu National Park (PNI), one of the few remaining areas of Atlantic forest protected by law, the sixth hydroelectric power plant named Baixo Iguaçu was built, which started in 2013, with operation beginning in 2019. The construction of this dam warns of potential impacts on fish fauna. As a research in the period prior to the implementation of the project, our aim was to present an updated list of fish fauna of the Lower Iguaçu River and tributaries, as well as to evaluate the trophic guilds and possible natural variations, in order to assist future studies in the investigation of impacts caused by the enterprise. Sampling was carried out monthly in 25 locations using several fishing gears, during the 2010 and from 2013 to 2016. 87,745 specimens, belonging to 74 species, were collected, distributed in eight orders, 22 families and 52 genera. The richest orders were Characiformes and Siluriformes (92% of the species). Regarding the origin of the species, 48% are indigenous, 39% alien, 9% exotic and 4% hybrid. The fish fauna was characterized by species of small and medium size. Eighteen large species occurred in both the tributaries and the main channel and about 4% of the species were classified as endangered. For the trophic guilds, six were categorized: detritivore, herbivore, insectivore, invertivore, piscivore and carnivore. We also infer that trophic guilds suffer interannual and spatial influences in our area and studied period. These variations in trophic guilds do not seem to be related to the construction of the dam. However, the post-damming effects can affect the natural dynamics that promote fluctuations in the proportions of the guilds. These results will contribute to the understanding of the future effects on the trophic structure of the fish fauna in the lower Iguaçu. Thus, our findings show essential results for future investigations that seek to reveal the influences that this impoundment may have caused on the diversity of species, as well as on the composition of trophic guilds.